Making Climate Forecasts Matter - National Research Council (The National Academies Press, 1999)
El Nino has been with us for centuries, but now we can forcast it, and thus can prepare far in advance for the extreme climatic events it brings. The emerging ability to forecast climate may be of tremendous value to humanity if we learn how to use the information well. How does society cope with seasonal-to-interannual climatic variations? How have climate forecasts been used—and how useful have they been? What kinds of forecast information are needed? Who is likely to benefit from forecasting skill? What are the benefits of better forecasting? This book reviews what we know about these and other questions and identifies research directions toward more useful seasonal-to-interannual climate forecasts. In approaching their recommendations, the panel explores: Vulnerability of human activities to climate. State of the science of climate forecasting. How societies coevolved with their climates and cope with variations in climate. How climate information should be disseminated to achieve the best response. How we can use forecasting to better manage the human consequences of climate change.
Keywords: Earth Sciences; Environment and Environmental Studies

Global Environmental Change: Research Pathways for the Next Decade - National Research Council (The National Academies Press, 1999)
How can we understand and rise to the environmental challenges of global change? One clear answer is to understand the science of global change, not solely in terms of the processes that control changes in climate and the composition of the atmosphere, but in how ecosystems and human society interact with these changes. In the last two decades of the twentieth century, a number of such research efforts—supported by computer and satellite technology—have been launched. Yet many opportunities for integration remain unexploited, and many fundamental questions remain about the earth's capacity to support a growing human population. This volume encourages a renewed commitment to understanding global change and sets a direction for research in the decade ahead. Through case studies the book explores what can be learned from the lessons of the past 20 years and what are the outstanding scientific questions. Highlights include: Research imperatives and strategies for investigators in the areas of atmospheric chemistry, climate, ecosystem studies, and human dimensions of global change. The context of climate change, including lessons to be gleaned from paleoclimatology. Human responses to—and forcing of—projected global change. This book offers a comprehensive overview of global change research to date and provides a framework for answering urgent questions.
Keywords: Environment and Environmental Studies; Earth Sciences

Human Dimensions of Global Environmental Change: Research Pathways for the Next Decade - National Research Council (The National Academies Press, 1999)
This publication is extracted from a much larger report, Global Environmental Change: Research Pathways for the Next Decade, which addresses the full range of the scientific issues concerning global environmental change and offers guidance to the scientific effort on these issues in the United States. This volume consists of Chapter 7 of that report, "Human Dimensions of Global Environmental Change," which was written for the report by the Committee on the Human Dimensions of Global Change of the National Research Council (NRC). It provides findings and conclusions on the key scientific questions in human dimensions research, the lessons that have been learned over the past decade, and the research imperatives for global change research funded from the United States.
Keywords: Behavioral and Social Sciences; Environment and Environmental Studies

U.S.-European-Japanese Workshop on Space Cooperation: Summary Report (The National Academies Press, 1999)

Revisiting Home Visiting: Summary of a Workshop - Institute of Medicine (The National Academies Press, 1999)
Keywords: Behavioral and Social Sciences

Adolescent Development and the Biology of Puberty: Summary of a Workshop on New Research - Michele D. Kipke (The National Academies Press, 1999)
Adolescence is one of the most fascinating and complex transitions in the human life span. Its breathtaking pace of growth and change is second only to that of infancy. Over the last two decades, the research base in the field of adolescence has had its own growth spurt. New studies have provided fresh insights while theoretical assumptions have changed and matured. This summary of an important 1998 workshop reviews key findings and addresses the most pressing research challenges.
Keywords: Behavioral and Social Sciences; Health and Medicine

Adequacy of Climate Observing Systems - National Research Council (The National Academies Press, 1999)
The 1997 Conference on the World Climate Research Programme to the Third Conference of the Parties of the United Nations Framework Convention on Climate Change concluded that the global capacity to observe the Earth's climate system is inadequate and is deteriorating worldwide. As a result, the chair of the subcommittee of the U.S. Global Change Research Program (USGCRP) requested a National Research Council study to assess the current status of the climate observing capabilities of the United States. This report focuses on existing observing systems for detection and attribution of climate change, with special emphasis on those systems with long time series.
Keywords: Earth Sciences; Environment and Environmental Studies

Selecting Instructional Materials: A Guide for K-12 Science - National Research Council (The National Academies Press, 1999)
The National Science Education Standards set broad content goals for teaching grades K-12. For science teaching programs to achieve these goals—indeed, for science teaching to be most effective—teachers and students need textbooks, lab kits, videos, and other materials that are clear, accurate, and help students achieve the goals set by the standards. Selecting Instructional Materials provides a rigorously field-tested procedure to help education decisionmakers evaluate and choose materials for the science classroom. The recommended procedure is unique, adaptable to local needs, and realistic given the time and money limitations typical to school districts. This volume includes a guide outlining the entire process for school district facilitators, and provides review instruments for each step. It critically reviews the current selection process for science teaching materials—in the 20 states where the state board of education sets forth a recommended list and in the 30 states where materials are selected entirely by local decisionmakers. Selecting Instructional Materials explores how purchasing decisions are influenced by parent attitudes, political considerations, and the marketing skills of those who produce and sell science teaching materials. It will be indispensable to state and local education decisionmakers, science program administrators and teachers, and science education advocates.
Keywords: Education

Measuring Functional Capacity and Work Requirements: Summary of a Workshop - Institute of Medicine; National Research Council (The National Academies Press, 1999)
The Social Security Administration (SSA) is reengineering its disability claims process for providing cash benefits and medical assistance to blind and disabled persons under the Social Security Disability Insurance (SSDI) program and the Supplemental Security Income (SSI) Program (Title II and Title XVI of the Social Security Act). As one element of this effort, SSA has proposed a redesigned disability determination process. The agency has undertaken a multi-year research effort to develop and test the feasibility, validity, reliability, and practicality of the redesigned disability determination process before making any decision about implementing it nationally. SSA requested the National Academy of Sciences to review and provide advice on its research relating to the development of a revised disability decision process, including the approach, survey design, and content of the Disability Evaluation Study (DES). One of the committee's tasks is to examine SSA's research into existing and other developing functional assessment instruments for the redesign efforts and to provide advice for adopting or developing instruments for the redesigned decision process and the DES.
Keywords: Health and Medicine

Serving the Needs of Pre-College Science and Mathematics Education: Impact of a Digital National Library on Teacher Education and Practice. Proceedings from a National Research Council Workshop (The National Academies Press, 1999)
Keywords: Education

Hydrologic Science Priorities for the U.S. Global Change Research Program: An Initial Assessment - National Research Council (The National Academies Press, 1999)
The availability of fresh water is potentially one of the most pervasive crises of the coming century. Water-related decisions will determine the future of major ecosystems, the health of regional economies, and the political stability of nations. A vigorous program of research in hydrologic sciences can provide the basis for sound water management at local, regional, national, and international levels. The Committee on Hydrologic Science was established by the National Research Council in 1999 to identify priorities for hydrologic science that will ensure its vitality as a scientific discipline in service of societal needs. This charge will be performed principally through a series of studies that provide scientific advice on the hydrologic aspects of national program and U.S. hydrologic contributions to international programs. This first report contains a preliminary assessment of the hydrologic science content of the U.S. Global Change Research Program (USGCRP). Because this is a short and focused report, little effort is spent to reaffirm the established and successful elements of the USGCRP. In fact, the Committee generally endorses the findings of the National Research Council (NRC) report Global Environmental Change: Research Pathways for the Next Decade (NRC, 1998a; the so-called Pathways report) in this respect. Instead the attention here is directed toward the most critical missing hydrologic science elements in the FY2000 USGCRP. This brings the focus to the terrestrial component of the water cycle. The integrative nature of terrestrial hydrology could significantly strengthen the USGCRP.
Keywords: Earth Sciences

Global Perspectives for Local Action: Using TIMSS to Improve U.S. Mathematics and Science Education - National Research Council (The National Academies Press, 1999)
The Third International Mathematics and Science Study (TIMSS) raised the alarm about U.S. mathematics and science education. Most Americans are now aware that U.S. students lag behind their peers in other developed nations. In one state, the legislature reacted by lengthening the school year, assuming that more time on academic content would boost student performance. Some educators have fixed the blame on the mathematics and science curricula typically used in U.S. schools. Does the problem lie in the curricula, instruction, or the system of support available to teachers? This book presents the first comprehensive analysis of TIMSS study—a half-million students from 15,000 schools around the world. It presents detailed reports on three major aspects of education, including curriculum issues, teaching practices, and school support.
Keywords: Education

Data and Methodological Issues for Tracking Former Welfare Recipients: A Workshop Summary (The National Academies Press, 1999)
Keywords: Behavioral and Social Sciences

Record Linkage Techniques -- 1997: Proceedings of an International Workshop and Exposition (The National Academies Press, 1999)
Keywords: Math, Chemistry, and Physics; Surveys and Statistics

Transforming Undergraduate Education in Science, Mathematics, Engineering, and Technology - National Research Council (The National Academies Press, 1999)
Today's undergraduate students—future leaders, policymakers, teachers, and citizens, as well as scientists and engineers—will need to make important decisions based on their understanding of scientific and technological concepts. However, many undergraduates in the United States do not study science, mathematics, engineering, or technology (SME&T) for more than one year, if at all. Additionally, many of the SME&T courses that students take are focused on one discipline and often do not give students an understanding about how disciplines are interconnected or relevant to students' lives and society. To address these issues, the National Research Council convened a series of symposia and forums of representatives from SME&T educational and industrial communities. Those discussions contributed to this book, which provides six vision statements and recommendations for how to improve SME&T education for all undergraduates. The book addresses pre-college preparation for students in SME&T and the joint roles and responsibilities of faculty and administrators in arts and sciences and in schools of education to better educate teachers of K-12 mathematics, science, and technology. It suggests how colleges can improve and evaluate lower-division undergraduate courses for all students, strengthen institutional infrastructures to encourage quality teaching, and better prepare graduate students who will become future SME&T faculty.
Keywords: Education

Global Perspectives for Local Action: Using TIMSS to Improve U.S. Mathematics and Science Education, Professional Development Guide - National Research Council (The National Academies Press, 1999)
The Third International Mathematics and Science Study (TIMSS) is a rich source of information that can be used by a broad range of stakeholders to promote discussions and actions to improve K-12 mathematics and science teaching and learning. To support educators, administrators, parents, and others interested in education in using TIMSS materials, the National Research Council (NRC) has prepared a report, Global Perspectives for Local Action: Using TIMSS to Improve U.S. Mathematics and Science Education (see "Resources"). This report will help educators, administrators, parents and others interested in education to understand what can be learned from TIMSS findings, and it will encourage them to use the information to make improvements in mathematics and science education. Provided in the report are insights into mathematics and science achievement, curriculum, instruction, and school support systems, such as professional development, in the United States and around the world. To make TIMSS information more accessible and useful to educators and the public, the NRC prepared this professional development guide to accompany its report. This guide provides directions and support materials for leading workshops and planning sessions for teachers, educational administrators, higher education faculty, and the interested public.
Keywords: Education

Improving Student Learning: A Strategic Plan for Education Research and Its Utilization - National Research Council (The National Academies Press, 1999)
The state of America's schools is a major concern of policymakers, educators, and parents, and new programs and ideas are constantly proposed to improve it. Yet few of these programs and ideas are based on strong research about students and teachers—about learning and teaching. Even when there is solid knowledge, the task of importing it into more than one million classrooms is daunting. Improving Student Learning responds by proposing an ambitious and extraordinary plan: a strategic education research program that would focus on four key questions: How can advances in research on learning be incorporated into educational practice? How can student motivation to achieve in school be increased? How can schools become organizations capable of continuous improvement? How can the use of research knowledge be increased in schools? This book is the springboard for a year-long discussion among educators, researchers, policy makers, and the potential funders—federal, state, and private—of the proposed strategic education research program. The committee offers suggestions for designing, organizing, and managing an effective strategic education research program by building a structure of interrelated networks. The book highlights such issues as how teachers can help students overcome their conceptions about how the world works, the effect of expectations on school performance, and the particular challenges of teaching children from diverse and disadvantaged backgrounds. In the midst of a cacophony of voices about America's schools, this book offers a serious, long-range proposal for meeting the challenges of educating the nation's children.
Keywords: Education

The Role of Diffusion Processes in Fertility Change in Developing Countries - National Research Council (The National Academies Press, 1999)
This report summarizes presentations and discussions at the Workshop on the Social Processes Underlying Fertility Change in Developing Countries, organized by the Committee on Population of the National Research Council (NRC) in Washington, D.C., January 29-30, 1998. Fourteen papers were presented at the workshop; they represented both theoretical and empirical perspectives and shed new light on the role that diffusion processes may play in fertility transition. These papers served as the basis for the discussion that is summarized in this report.
Keywords: Behavioral and Social Sciences

Critical Perspectives on Schooling and Fertility in the Developing World - National Research Council (The National Academies Press, 1999)
This volume assesses the evidence, and possible mechanisms, for the associations between women's education, fertility preferences, and fertility in developing countries, and how these associations vary across regions. It discusses the implications of these associations for policies in the population, health, and education sectors, including implications for research.
Keywords: Behavioral and Social Sciences

Work-Related Musculoskeletal Disorders: Report, Workshop Summary, and Workshop Papers - National Research Council (The National Academies Press, 1999)
Estimated costs associated with lost days and compensation claims related to musculoskeletal disorders—including back pains and repetitive motion injuries—range from $13 billion to $20 billion annually. This is a serious national problem that has spurred considerable debate about the causal links between such disorders and risk factors in the workplace. This book presents a preliminary assessment of what is known about the relationship between musculoskeletal disorders and what may cause them. It includes papers and a workshop summary of findings from orthopedic surgery, public health, occupational medicine, epidemiology, risk analysis, ergonomics, and human factors. Topics covered include the biological responses of tissues to stress, the biomechanics of work stressors, the epidemiology of physical work factors, and the contributions of individual, recreational, and social factors to such disorders. The book also considers the relative success of various workplace interventions for prevention and rehabilitation.
Keywords: Industry and Labor; Health and Medicine; Behavioral and Social Sciences